Biological Characteristics of West Nile Virus and Its Correlation with the Development of Antiviral Drugs and Vaccines - Diana Nurjanah; N L P I Dharmayanti (Indonesian Center for Animal Research and Development, 2019)
West Nile virus (WNV) is a zoonotic RNA virus. Its genome encodes 3 structural and 7 non-structural proteins. Mutations can occur in both structural and non-structural proteins of the virus. Mutations can enhance the pathogenicity and virulence, but some mutations are beneficial for the development of vaccines. Licensed vaccines are only available for horses, while vaccines for humans are still under development. In Indonesia, WNV infection was detected in 2014 in West and East Java, but vaccines and antiviral drugs in both animals and humans are not yet available. This review describe the characteristic of structural and non-structural proteins of WNV and its correlation with mutations and the development of vaccines and antiviral drugs. Molecular identification and further research is needed to predict, prevent and control WNV infections in vectors, susceptible animals and humans.